Analisis Peran Guru Dalam Pembelajaran Seni Musik di Sekolah Dasar Terhadap Siswa Kelas V Tahun 2021 - Listari, Ayu; Imansyah, Farizal; Marleni, Marleni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Analysis of Teacher's Role in Musical Arts Learning in Elementary Schools for Class V Students in 2021. The purpose of this study was to find out how the role of teachers in learning music arts in Elementary Schools for Class V students in 2021. This research method used descriptive qualitative. This data collection technique uses documentation, observation and interviews. The results showed that 1) The results of observations through observations with the help of the APKG 2 (Teacher Ability Assessment Tool 2) showedthat music learning in the classroom had the teacher's ability in teaching music not optimal, while the results of field observations through observation sheets showed that the role indicators the teacher as a demonstrator in learning the art of music class V is in the high category, on the indicator of the teacher'srole as a class manager in learning the art of music is in the high category; The indicator of the teacher's role as a mediator in learning the art of music is in the high category. In the indicator of the teacher's role as a facilitator, it is in the medium category. 2) The results of the interview regarding the indicator of the teacher as a demonstrator stated that limited knowledge of the art of music became a barrier for teachers tocarry out music learning in the classroom. In the indicators of the teacher's role as class processors, it is explained that there are some teachers who claim to still have difficulties in managing the class and 3) The results of the analysis of the documentation data can be concluded that the facilities and infrastructure orfacilities at the 09 Sungai Are State Elementary School can support the teaching and learning process, especially facilities for music lessons. However, these facilities and infrastructure are not yet complete.